Pushing boundaries in cardiac surgery: minimally invasive mitral valve repair combined with tricuspid valve repair and/or other concomitant procedures - Stelzmueller, Marie-Elisabeth; Zilberszac, Robert; Rosenhek, Raphael; Hutschala, Doris; Kappel, Sabine; Lassnig, Andrea; Laufer, Guenther; Zimpfer, Daniel; Wisser, Wilfried (Frontiers in Cardiovascular Medicine, 2024)
Introduction Minimally invasive mitral valve repair/replacement has emerged as a widely accepted surgical approach for managing mitral valve disorders. Continuous technological progress has contributed to the refinement of this procedure, leading to improved safety, decreased surgical trauma, and faster recovery times. Despite these advancements, there remains a scarcity of data concerning minimally invasive complex mitral valve repair surgeries when combined with additional procedures. Methods Between November 2008 and December 2022, 153 patients underwent an operation using a minimally invasive technique. All patients underwent mitral valve surgery for severe mitral valve insufficiency/stenosis in combination with at least one additional procedure for tricuspid valve repair (n = 52, 34%), patent foramen ovale or atrial septal defect closure (n = 34, 22.2%), left atrial appendage occlusion (n = 25, 16.3%), or electrophysiological procedure (n = 101, 66.0%). Two concomitant procedures were conducted in 98 patients (64.1%), three concomitant procedures in 49 patients (32%), and four concomitant procedures in 6 patients (3.9%). Results Surgical success was achieved in 99.3% of the patients (n = 152), one patient required a revision of the mitral valve repair on the first postoperative day due to systolic anterior motion phenomenon. Mitral valve repair was performed in 136 patients (88.9%), while 15 patients (9.8%) received a mitral valve replacement as per a preoperative decision due to severe mitral valve stenosis, and two patients (1.3%) underwent other mitral valve procedures. Therapeutic success in treating atrial fibrillation was achieved in 86 patients (85.1%) of the 101 who received an additional maze-procedure. The 30-day mortality rate was 0.7%, with one patient succumbing to respiratory failure. Neurological complications occurred in 7 patients (4.6%). Freedom from reoperation was calculated as 98% at 5-year follow-up and 96.5% at 10-year follow-up. Conclusion Minimally invasive mitral valve surgery, even when performed alongside concomitant procedures, stands out as a reproducible and safe technique with outstanding outcomes. It is imperative to advance towards the next frontier in minimally invasive surgery, encouraging experienced surgeons to undertake more complex procedures using minimally invasive approaches. These results help envision extending the boundaries of minimally invasive surgery by performing complex mitral valve procedures and associated interventions entirely through endoscopic means in suitable patients.